IMPLIKASI BERLAKUNYA UNDANG-UNDANG NOMOR 3 TAHUN 2020 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 4 TAHUN 2009 TENTANG PERTAMBANGANMINERAL DAN BATUBARA DALAM PENGAWASAN PERTAMBANGAN RAKYAT GALIAN BATUAN - MARTA KUSMIARI; Mexsasai Indra; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
A state or government exists to ensure the welfare of its people, so it is necessary to supervise the management of natural resources. Supervision in the natural resource management sector is important in Indonesia, this is in accordance with the mandate in Article 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945). Supervision of the mining natural resource sector, especially community mining of rock excavation, is the authority of the state as control over mining and the government as the executor of the supervisory authority. Supervision of mining has undergone many changes in accordance with the issuance of regulations in new regulations, the latest Law, namely Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining, reinstating the authority of the provincial government by revoke the authority over the concurrent affairs of the regional government over mining, so that the authority over mining is carried out or regulated directly by the central government.This type of legal research can be categorized as normative-empirical legal research with the live case study category, the live case study approach is an approach to a legal event that is still in progress or has not ended. The data sources used are secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The data collection technique comes from the literature study method, after the data is collected, conclusions are drawn.From the results of the study obtained 2 (two) main things, namely first the central government wishes to build a licensing system in the mining sector as well as possible with the new Mining Law, secondly the changing authority system which in accordance with the applicable regulations causes many problems in terms of supervision and licensing in the mining sector. The researcher's suggestions are first to improve Human Resources who play an important role in the mining sector so that the desired system can be achieved, secondly to coordinate in terms of mining supervision with local governments in regional regulations.Keywords: People's Mining Rock Quarry – Supervision -Authority